Pemanfaatan Framework Codeigniter Dalam Pengembangan Aplikasi Reporting Research - Asep Saifudin; Meri Mayang Sari; Asaidha Kuncoro (UNIVERSITAS RAHARJA, 2022)
Technological developments continue to grow rapidly. in any field such as economic, social, transportation and others participate in technological developments. Many consumers demand industrial development to be able to meet all their needs quickly and with quality, so we need a facility that can assist in carrying out the production of the intended needs. Currently the running system is still using Microsoft Excel in making reports in the furniture production sector, this section really needs a technology that can facilitate its work effectively and efficiently. In making reports, officers experience difficulties so that it takes a long time and prior to processing, they must obtain approval from the supervisor in charge so that they can be processed to the next stage, namely the production stage. then we need a system as a medium to assist officers in making reports and make it easier to approve reports and provide convenience to officers in finding and storing data that has been made. The framework used in designing reporting research applications is the CodeIgniter framework as a framework for creating a system or application, the programming language uses Javascript, CSS and PHP. With this application, it is hoped that the system can provide a sense of comfort in working and ease of reporting.